Identifying and Implementing Performance KPIs Using the Socratic Questioning Method: A quasi-experimental field study - Abdolali Ahmadzahi Torshab; Hassan Danaeefard; Ahmad Ali Khaefelahi; Asadollah Ganjali (پژوهش‌های مدیریت عمومی, 2023)
Extended Abstract Abstract  The purpose of this study is to design and implement an effective performance management system in a public financial Fund using the Socratic method and dialogues. The first stage of the study seeks to intervene using this method while identify performance criteria and indicators and in the second stage, based on the findings of the previous stage, the purpose is to investigate the impact of interventions on staff performance, employees' perception of supervisor’s behaviors in the performance management process, and PM-related behavioral and attitudinal consequences.As an explorative mixed method, this study has used the method of dialogue and questioning approach as an intervention technique to extract the key criteria and performance indicators. In the second stage, in order to investigate the effect of the interventions, a quasi-experimental design with unequl groups consisting of three experimental groups, control 1 and control 2 was used. A sample of 166 people was selected from the three groups so that 53 people were selected for the intervention group, 68 people for the control group 1, and 45 people for the control group 2. In the qualitative stage, performance criteria were identified, reviewed, and modified. In the quasi-experimental study section, post-test results showed that employees who effectively participated in the process of designing and implementing the performance management system performed better than the control groups.Introduction New conditions in public organizations, including lack of satisfaction with government performance and environmental pressure for high-quality services from the public, requires a paradigm shift from a traditional and focused perspective of the performance to a result-based and customer-oriented performance management system (PSM) (Lin and Lee, 2011). Moynihan (2008) shows that multiple stakeholders can interpret performance data from different perspectives, which can lead to different outputs and results. Divers stakeholders' participation and dialogues in the performance management process help to improve performance with a variety of feedbacks (Hörisch et al., 2015). However, Current approaches to performance dialogues does not include diverse perspectives, flexibility, and contextual limitations of public organizations (Pulakos et al., 2015). It is argued that implementing an effective PSM in the public sector requires different metrics for all tasks and participation of various internal and external stakeholders (Deschamps & Mattijs, 2018; Verbeeten, 2008). The Socratic questioning dialogues supports a fluid and dynamic view and considers multiple perspectives. By engaging different participants in the dialogues, firstly this research seeks to identify performance indicators and KPIs, and secondly by implementing the system it tries to investigate its effect on employee’s performance and PM-related attitudes and outcomes.  Case study The population of the study was a public Fund consisted of 250 employees. A sample of 166 full-time employees was selected in the experiment and control groups. The number of participants for control group 1 and control group 2 was 45 and 68 people respectively, while for the experiment group it was 53 participants.  Materials and Methods Grounding the study in constructive theory, the Socratic questioning and dialogues as a reflective and thoughtful approach were adopted to acquire the performance indicators and KPIs. In order to facilitate the design and implementation of the performance management, this study aims to use a quasi-experimental design with three control, comparison, and intervention groups in a public Fund of over a 3-years study. ANOVA was used to analyze the research data.Discussion and Results In the qualitative phase, PM indicators and KPIs were identified. In the quantitative phase, results indicated that employees who participated in the experiment experienced a higher level of performance, perceived desirable supervisor’s behaviors related to the PM process, and showing better PM-related outcomes than control groups. Although the performance of the control groups in some conditions due to a lower level intervention is improved, the performance of both control groups remained constant.ConclusionThe results of a field study using the Socratic questioning with three groups in a public Fund were provided. Findings indicated that the experimental group performance has significantly increased than control groups. This research indicated the significant role of the questioning and dialogue method in designing and implementing the performance management.